A General Strategy for the Synthesis of Hierarchically Ordered Metal–Organic Frameworks with Tunable Macro‐, Meso‐, and Micro‐Pores. Issue 3 (21st November 2022) - Wang, Chen; Zhang, Heyao; Wang, Yao; Wu, Jie; Kirlikovali, Kent O.; Li, Peng; Zhou, Yaming; Farha, Omar K.
Abstract: Hierarchically ordered porous materials with tailored and inter‐connected macro‐, meso‐, and micro‐pores would facilitate the heterogeneous adsorption and catalysis processes for a wide range of applications but remain a challenge for synthetic chemists. Here, a general and efficient strategy for the synthesis of inverse opal metal–organic frameworks (IO MOFs) with a tunable size of macro‐, meso‐, and micro‐pores is reported. The strategy is based on the step‐wise template formation, precursor infiltration, solvo‐thermal reaction, and chemical etching. As a proof of the general applicability of this strategy, a series of inverse opal zirconium‐based MOFs with intrinsic micro‐ and/or meso‐pores, including UiO‐66, MOF‐808, NU‐1200, NU‐1000 and PCN‐777, and tunable macropores (1 µm, 2 µm, 3 µm, 5 µm, and 10 µm), have been prepared with outstanding yields. These IO MOFs demonstrate significantly enhanced absorption rates and faster initial hydrolysis rates for organophosphorus (OPs) aggregates compared to those of the pristine MOFs. This work paves the way for the further development of hierarchically ordered MOFs for advanced applications. Abstract : A general and efficient synthesis strategy affords inverse opal metal–organic frameworks (IO MOFs) with a tunable size of macro‐, meso‐, and micro‐pores. The strategy is based on the step‐wise template formation, precursor infiltration, solvo‐thermal reaction, and chemical etching. These IO MOFs demonstrate significantly enhanced organophosphorus (OPs) aggregate absorption rates relative to those of the pristine MOFs.